2018
DOI: 10.1093/pubmed/fdy178
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity, weight and wellbeing outcomes among attendees of a weekly mass participation event: a prospective 12-month study

Abstract: Background Mass participation events are recognized as a way of engaging low-active individuals in health-enhancing physical activity, but there is a need to investigate the sustained effects on behaviour and health. This study aimed to examine changes in self-reported physical activity, weight and wellbeing over 12 months in participants of parkrun, a weekly mass participation 5 km running event. Methods New parkrun registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…The impacts of parkrun on physical activity outcomes were assessed by two UK quantitative studies: one cross-sectional ( Stevinson and Hickson, 2014 ), and one prospective longitudinal design ( Stevinson and Hickson, 2019 ), both of which matched survey responses with (longitudinal) parkrun administrative data. Stevinson and Hickson (2014) surveyed a large representative sample of parkrunners (n = 7308 adults) and found improvements in cardiorespiratory fitness from first participation occasion to their fastest parkrun time in the survey year; age-adjusted time improved on average by 10%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of parkrun on physical activity outcomes were assessed by two UK quantitative studies: one cross-sectional ( Stevinson and Hickson, 2014 ), and one prospective longitudinal design ( Stevinson and Hickson, 2019 ), both of which matched survey responses with (longitudinal) parkrun administrative data. Stevinson and Hickson (2014) surveyed a large representative sample of parkrunners (n = 7308 adults) and found improvements in cardiorespiratory fitness from first participation occasion to their fastest parkrun time in the survey year; age-adjusted time improved on average by 10%.…”
Section: Resultsmentioning
confidence: 99%
“…Arguably, the strongest evidence for the physical benefits of parkrun was captured by Stevinson and Hickson (2019) in their prospective study of n = 878 newly registered adults ( Stevinson and Hickson, 2019 ). At 6 months, 63% and at 12 months 53% were still attending parkrun with no statistically significant differences at baseline between survey completers and non-completers ( Stevinson and Hickson, 2019 ). New registrants were already highly active with only 8.8% (n = 31) classified below the minimum recommendation for moderate-to-vigorous–intensity physical activity (MVPA).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that depression, tension, isolation and anger decreased, while participants' self-esteem, mood and stress levels improved (44,45). According to Stevinson et al (46) happiness and stress reduction were maintained 1 year after starting Parkrun (47). In Australia, well-being improvement was limited to older runners.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 The organisation has been widely praised as being successful in encouraging participation particularly in individuals who were previously inactive. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%